Synthesis and electrochemical performance of MoO2/graphene nanomaterials as anode for lithium-ion battery - Tu, Nguyen Van; Xue, Yang (Vietnam Journal of Chemistry, 2017)
In this articles, molybdenum dioxide/graphene composites were successfully prepared by a hydrothermal method. The results indicated graphene composition affects the properties of the electrochemical electrode, increased to 10 wt%, the molybdenum dioxide particles were uniformly deposited on the graphene sheets. The samples used as the electrode material for lithium batteries; it exhibited high reversible specific capacities of 1267 mAhg-1 at the second cycle and 629 mAhg-1 after 60 cycles. The outstanding electrochemical performance of the composite can be attributed to the synergistic interaction between molybdenum dioxide and graphene. There were enough void spaces to buffer volume change in the structure. Furthermore, graphene nanosheets in the hybrid material could act as not only lithium storage electrodes but also electronic conductive channels to improve the electrochemical performances. Keywords. Molybdenum dioxide, graphene composites, lithium-ion batteries.